3D AutoLISP Mesh Generation - Dirhar, Mohammed Amine; Kennassi, Essaid El; Janati, Khalid Idrissi; Bousshine, Lahbib (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
This work is the result of 3D mesh generation AutoLISP’s code. We create the code for parallelepiped shape and we generate the x, y, z coordinates for each vertex. We obtain for the mesh generation: coordinates, nodes, and elements. This data is affected to a data structure file. The results obtained can be directly used for engineering need.